(untitled) (American International Journal of Economics and Finance Research, 2023)
This study aims to systematically review the previous literature on the drivers influencing internal audit effectiveness and coherent these drivers in a conceptual model. A ‘systematic literature review (SLR)’ is performed to detect the drivers that influence internal auditing more effectively. Relevant past literature is swotted between January 2005 to July 2022 as considered the important drivers affecting internal audit functions’ effectiveness. Apart from these, all the guidelines mentioned in the international standards regarding internal audit given by the Institute of internal audit (IIA) have also been considered in this study. Three important outcomes are identified for the internal audit function to be effective: meeting the expectation of management, meeting the expectation of the audit committee, and meeting the expectation of auditees. Moreover, based on the SLR, ten important drivers are identified that mostly affect the internal audit effectiveness, such as culture, management support, audit committee support, organizational size, professional qualification, independence, working environment, internal audit budget, employee rotation policy, and proficiency of internal auditors. Based on the identified drivers and outcomes of internal audit effectiveness, this study proposed a conceptual model for internal audit effectiveness. The proposed conceptual model encourages the regulator, policy maker, and different stakeholders to make appropriate strategic decisions to make their internal audit department more effective. JEL Classification Codes: M40, M41, M42, H83, F65,